RELATIONSHIP OF NUTRITION KNOWLEDGE AND MACRONUTRIENT INTAKE WITH NUTRITION STATUS ATHLETES - Demsa Simbolon; Riska Oktavia; Arie Krisnasary (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
An athlete needs to pay attention to the amounts of nutrients that give the body energy. If an athlete doesn't know much about proper nutrition, it can make them less aware of how important it is to eat healthy food. Indonesian athletes who aren't performing well are doing so because they aren't getting enough healthy nutrition. This is because their teachers don't know how nutrition can help athletes perform better. The study aimed at investigating the relationship between nutritional knowledge and macronutrient intake with the nutritional status of athletes. Analytic descriptive research with a cross sectional approach. There were 94 athletes as the population, and a sample of 63 athletes in the dormitory involved, through simple random sampling method. The instruments used were the respondent's identity, nutritional knowledge questionnaire, 3x24 hour food recall, height measurement using microtoice and weight using digital scales, then the analysis of the data was conducted with 3 stages, namely univariate, bivariate analysis with chi square test and multivariate analysis with linear regression test. The results identified a relationship between nutritional knowledge (p=0.012) and macronutrient intake, namely energy intake (p=0.029), protein intake (p=0.001) with the nutritional status of athletes. Nevertheless, the study findings revealed no significant relation between fat consumption (p=0.781) and carbohydrate intake (p=0.927) and the nutritional condition of athletes. The most influential factor on nutritional status is energy intake. The greater the amount of energy intake, the greater the tendency to have more nutritional status. Therefore, it is crucial to implement the nutrition education to athletes in relation with nutritional intake and feeding based on balanced nutrition menu guidelines according to the needs of athletes.